Manajemen Anestesi pada Pasien Hamil G1P0 UK 26 Minggu Yangmenjalani Craniotomy Removal Tumor Fossa Posterior - Sudadi; Kurniawaty, Juni; Utomo, F uad Cipto (Jurnal Komplikasi Anestesi, 2022)
Brain tumor during pregnancy are very rare and presents several challenges to the neurosurgeons, obstetricians and anaesthesiologist in not only establishing the diagnosis, but also in the perioperative management as it requires a careful plan to balance both maternal and fetal well-being. We report the anaesthetic management of a 26-week pregnant patient with brain tumor meningioma. As the patient was 26 weeks pregnant with sign and symptoms of raised intracranial pressure (ICP) with progressive neurological deficits, not manageable with drugs, elective craniotomy was planned for decompression of the brain tumor. We held a multidisciplinary meeting before the operation and made a detailed plan for how to proceed. During the operation, our team ensured intensive monitoring, provided adequate oxygen and achieved hemodynamic stability. Anaesthetic drugs like fentanyl, rocuronium, propofol and sevoflurane were carefully chosen in order to ensure the safety of both the mother and fetus. Under the careful and successful anaesthetic management, the patient underwent the surgery smoothly neither the mother nor baby experienced pre- or post-operative complications. Neurosurgeries in pregnancy are sparse, and careful planning with cross-disciplinary specialist was need in advanced of the operation. Moreover, when dealing with such surgeries, we should consider the safety of both the mother and fetus, which challenging but important.